ANALYSIS OF MOTION DETECTION IN VIDEO SECURITY SURVEILLANCE SYSTEM - HADRI, MASHAZRINA (2017)
From video sequences, motion detection algorithm can be applied to detect any abnormal behavior, and to recognize the crime using flow of process of behavior recognition. In order for surveillance system to detect abnormal behavior, there is one parameters known as baseline. Value of baseline is calculated by the system according recorded information. The baseline value is viewed as abnormal when the benchmark value is higher than upper limit or lower than the lower limit of the calculated baseline. The system evaluate the relationship of abnormal baselines and decide to choose that recognized moving object has abnormal conduct or ordinary conduct. After the system are check and abnormal behavior was distinguished, the system will creates alarm to alert regarding that situation. There are few appearances that need to consider in order to avoid an error such as occlusion, brightness of surrounding and noise.